VD_FINDINFO Décision / 2018 / 535 vom 4. Juli 2018 - VD Tribunal cantonal (2018)
ORDONNANCE PÉNALE, FICTION DE LA NOTIFICATION, OPPOSITION TARDIVE | 354 CPP (CH), 356 al. 2 CPP (CH), 85 al. 4 CPP (CH)